Three-dimensional particle-in-cell simulation of fast oscillation startup and efficiency improvement in a relativistic magnetron with electric priming - Maurya S.; Singh V.V.P.; Jain P.K. (My University, 2025)
A 3-D particle-in-cell (PIC) code MAGIC 3-D has been used to examine the output performance of a relativistic magnetron operating under the effect of electric priming by protrusions and recessions on the inner surface of the anode vanes. Electric priming has been implemented and demonstrated using the PIC code for electron prebunching in A6 relativistic magnetron. When N-fold perturbation of the radial electric field is imposed in the azimuthal direction along anode-vane inner surfaces, the electron initially develops into the desired 2π-mode, resulting in fast oscillation startup. The startup time is reduced by 46%, the output power is increased by 30%, and the efficiency is increased by 30% for three protrusions alternating with three recessions along the anode-vane inner surfaces in comparison with the A6 basic model. Simulations have been also carried out for different combinations of protrusions and recessions. All the studies have been carried out for 2π-mode of operation. © 2012 IEEE.